Analisis Supply Chain dan Nilai Tambah Carica pubescens - Azizi, Ernes Septina; Falatehan, Faroby (UNIVERSITAS LABUHANBATU, 2023)
Kejajar District is the largest carica producer in Wonosobo Regency. With the average yield obtained, it is considered not very profitable because farmers get low prices, even though prices at the consumer level are considered expensive. So the authors conducted research with the aim of analyzing the supply chain of carica and analyzing the added value of carica into sweets. The results of the value chain analysis show that there are 5 actors, namely farmers, village collectors, district collectors, outside retailers and processing industries. In improving the value chain, for the processing industry it can be improved through processing that prioritizes quality, service and marketing is more attractive. The results of the added value analysis show that processing carica into sweets provides benefits. In confectionery production, part of the margin received by the industry is distributed by the contribution of other inputs, namely 65 percent, processing profit by 41 percent and labor income by 16 percent. The total margin for Candied Carica is IDR 10,630.00.Â Keywords : Carica, Hayami, Supply Chain, Value Added